Developing guided inquiry module in animal reproductive system material - Nosi Qadariah; Sri Rahayu Lestari; Fatchur Rohman (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Guided inquiry module is one of alternative to improve students’ science process skills and cognitive learning outcomes. The aim of this research was to produce guided inquiry module in animal reproductive system material as well as improving student science process skills and cognitive learning outcomes. The research used ADDIE development model which consists of the following stages: analyze, design, develop, implement, and evaluation. The research instruments for collecting the data included material and media expert validation sheets, field practitioner questionnaire, module practicality questionnaire, pretest and posttest question sheets (used to measure science process skills and cognitive learning outcomes). The data analysis technique used were quantitative and qualitative descriptions as well as quade's rank analysis of covariance. The results of content and media expert validations were 94.84%  and 92.43%  respectively. In addition, the field practitioner response reached 95.7% and the module practicality value was 91.3%. Furthermore, the module has significantly improved students’ science process skills [F(1,78) = 42.509, p < 0.05] and  cognitive learning outcome  [F(1,78) = 7.480, p < 0.05]. Hence, the module is recommended to be implemented in delivering animal reproductive system.